ANALISIS GENRE FILM HOROR KOMEDI INDONESIA DALAM FILM “AGAK LAIN” KARYA MUHADKLY ACHO - Mardiah, Mardiah; Yuliana, Azmi; Wardah, Yulia; Siahaan, Hasnah (HIBRUL ULAMA, 2024)
Researchers took the comedy horror film entitled "Agak Laen" by Muhadkly Acho (2024) to analyze a genre in the film. This analysis aims to find out how many genres are used in the film "Agak Laen". The method used is a qualitative approach, which focuses on analyzing the characteristics of film genres to examine media data using a scheme from the basic elements of Nick Lacey's repertoire of elements. The repertoire of elements that will be analyzed by researchers are narrative or plot, characters, setting, iconography and style. The results of this research show that there are several genre characteristics or reportoire of elements in the film "Agak Laen" and it is true that this film is a horror comedy genre so it attracts a lot of interest from audiences of various ages, because for those behind this horror film it is certain there are elements of comedy that can provoke the audience to laugh out loud, apart from being suspenseful, this film also provokes humor to entertain the audience.